Quinazoline Derivatives as Potential Therapeutic Agents in Urinary Bladder Cancer Therapy - Wdowiak, Paulina; Matysiak, Joanna; Kuszta, Piotr; Czarnek, Katarzyna; Niezabitowska, Ewa; Baj, Tomasz (Frontiers in Chemistry, 2021)
Derivatives of quinazolines constitute a large group of chemicals with a wide range of biological properties. The character of quinazolines depends mostly on the properties of the substituents and their presence and position in one of the cyclic compounds. Derivatives of quinazoline are commonly used for treatment in medicine. Many of them are approved for antitumor clinical use, e.g.: erlotinib, gefitinib, afatinib, lapatinib, vandetanib. New quinazoline-based compounds are designed and synthesized as potential drugs of anticancer potency against bladder cancers. A very promising direction in bladder cancer treatment is targeted therapy directed at specific molecular pathways.